2005
DOI: 10.1038/sj.ejcn.1602332
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a questionnaire to assess fruit and vegetable intake in adults

Abstract: Objective: To validate a method for assessing fruit and vegetable intake among adults in a population of low intake. The method assesses mean intake and ranks individuals by their usual intake. Design: A precoded fruit and vegetable Questionnaire included a 24-h recall and a food frequency. The participants filled in the Questionnaire, a week later they started a 7-day food record, 1-day weighed record and 6 days using household measures. Subjects: Following advertisements 40 participants were recruited, 36 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 20 publications
2
60
1
Order By: Relevance
“…This dietary assessment showed high reliability and validity. The results have been presented elsewhere (19,20) . An overview of the variables assessed, and the children's and parents' questions on determinants of fruit and vegetable consumption, is presented in Table 1.…”
Section: Instrumentmentioning
confidence: 99%
“…This dietary assessment showed high reliability and validity. The results have been presented elsewhere (19,20) . An overview of the variables assessed, and the children's and parents' questions on determinants of fruit and vegetable consumption, is presented in Table 1.…”
Section: Instrumentmentioning
confidence: 99%
“…However, the instrument had good agreement with 24-HDR in a sample of Spanish children (135) and has been demonstrated to be reproducible (145) . The Pro-Children instrument, when compared with 7 d (130) and 1 d (42) diet records, was reported to have moderate to good validity for ranking individuals according to usual intake and was reproducible (42) . The ToyBox study instrument was shown to be reproducible and was reported to have moderate relative validity when compared with 3 d diet records (137) .…”
Section: Not Conducted Among European Populationmentioning
confidence: 99%
“…No details ‡ The reliability and content validity of the child questionnaires were tested separately in all participating countries (143) Reliability tested using a test-retest design was used by comparing data from two completions of the questionnaire conducted 1 week apart (130) No reliability data for F&V EYHS (30,117) Cross-sectional Children (n ≈ 4000) 9 and 15 years 4 (Denmark, Portugal, Estonia, Norway) (sourced study involves only Sweden)…”
Section: Ffq † (Based On Netherlands Cohort Study Ffq)mentioning
confidence: 99%
See 1 more Smart Citation
“…The instruments were translated into national languages (and translated back to English) taking into account the cultural appropriateness for the subjects, and tested for reliability and validity in multiple pilot tests prior to final administration. More details about this are given elsewhere [27,28,29]. …”
Section: Methodsmentioning
confidence: 99%